2000
DOI: 10.1067/mnc.2000.105634
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and quality of life in patients with normal rest thallium-201/stress technetium 99m-tetrofosmin dual-isotope myocardial SPECT

Abstract: Patients with normal results on dual-isotope myocardial perfusion scintigraphy, performed with Tc-99m-tetrofosmin for the stress images, have an excellent prognosis. Furthermore, our results suggest that Tl-201 cross talk in the Tc-99m window may be low and functionally and clinically unimportant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…20 Published prognostic studies performed in the USA in patients who underwent pharmacologic stress indicate that such patients are considered at higher risk. [6][7]23 Therefore, the annualized hard event rate of 0.63% for the present study's population is as low as that of studies conducted in the USA. [4][5][6] Risk stratification is essential to the development of evidence-based strategies for improved patient care in medicine.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…20 Published prognostic studies performed in the USA in patients who underwent pharmacologic stress indicate that such patients are considered at higher risk. [6][7]23 Therefore, the annualized hard event rate of 0.63% for the present study's population is as low as that of studies conducted in the USA. [4][5][6] Risk stratification is essential to the development of evidence-based strategies for improved patient care in medicine.…”
Section: Discussionmentioning
confidence: 88%
“…2,33 Prognostic values of left ventricular functional parameters using QGS have been demonstrated by multiple studies. [1][2][3][4][5][6][7][8][9]23,36 Previous studies found that post-stress LVEF and post-stress ESV assessed during gated SPECT had incremental predictive value in predicting cardiac death. In part, normal myocardial perfusion imaging was associated with a very low likelihood of cardiac death or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior reports indicated that patients with normal or near-normal stress perfusion have an excellent prognosis [11][12][13][14][15][16]. According to all these studies, the outcome of patients with normal perfusion is excellent, and the same is true for those with very mild perfusion abnormalities.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Groutars et al 29 reported good outcome in patients with normal perfusion studies. The annual event rate was 0.8% for any cardiac events.…”
Section: Prognostic Value Of Perfusion Datamentioning
confidence: 99%
“…Our results underscore previously published data on the prognostic value of gated SPECT imaging. [26][27][28][29][30][31][32][33][34] Sharir et al 9 showed that perfusion variables and ESV were powerful markers in the prediction of total coronary events, whereas in the prediction of CD, poststress LVEF and ESV were independent predictors and had incremental value over perfusion data. According to their criteria, patients were at increased cardiac risk when they had an LVEF \ 45% and an ESV [ 70 mL.…”
Section: Prognostic Value Of Functional Datamentioning
confidence: 99%